2005
DOI: 10.1073/pnas.0503239102
|View full text |Cite
|
Sign up to set email alerts
|

Replaceable neurons and neurodegenerative disease share depressed UCHL1 levels

Abstract: Might there be systematic differences in gene expression between neurons that undergo spontaneous replacement in the adult brain and those that do not? We first explored this possibility in the high vocal center (HVC) of male zebra finches by using a combination of neuronal tracers, laser capture microdissection, and RNA profiling. HVC has two kinds of projection neurons, one of which continues to be produced and replaced in adulthood. HVC neurons of the replaceable kind showed a consistent and robust underexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 45 publications
(51 reference statements)
2
31
0
1
Order By: Relevance
“…annotated database, microarrays, and a gene-manipulation tool for molecular investigations in songbirds. Relative to our preliminary (15) and other recent efforts (7,16), an important feature is that we ensured an array that contains cDNAs representing transcripts from multiple animal states and that there is a mostly full-length collection of these cDNAs. Once a cDNA of interest was identified, the full-length cds of the cDNA allowed us to perform overexpression experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…annotated database, microarrays, and a gene-manipulation tool for molecular investigations in songbirds. Relative to our preliminary (15) and other recent efforts (7,16), an important feature is that we ensured an array that contains cDNAs representing transcripts from multiple animal states and that there is a mostly full-length collection of these cDNAs. Once a cDNA of interest was identified, the full-length cds of the cDNA allowed us to perform overexpression experiments.…”
Section: Discussionmentioning
confidence: 99%
“…These fundamentals are difficult to study at a molecular level in songbirds because of the lack of high-throughput molecular and gene-manipulation tools for studying songbirds. Song production is associated with a rapid immediate early gene-expression response in vocal nuclei (4), where only three genes (egr-1 or ZENK, c-fos, and BDNF) up-regulated by singing had been identified when we began this project (4-6); two others (UCHL1 and Arc) were recently reported (7,8). Of these, full-length songbird cDNA clones are available only for UCHL1.…”
Section: Fig 1 Molecular Functions and Variant Analysis (A)mentioning
confidence: 99%
“…Recent reports also showed that UCH-L1 protein is involved in the survival of other types of neuronal cells. In birds and mice, upregulation of UCH-L1 is associated with increased survival of replaceable neurons, which continue to be produced and replaced in adulthood (Lombardino et al 2005). Moreover, transduction of exogenous UCH-L1 protein protected against b-amyloid-induced synaptic dysfunction of hippocampal neurons in vitro and improved the retention of contextual learning in a mouse model of Alzheimer's disease (Gong et al 2006).…”
Section: Ile93metmentioning
confidence: 99%
“…Addressing differences in gene expression in adult-born neurons can be achieved with laser capture microdissection (LCM). LCM has recently been used to demonstrate differential gene expression in replaceable vs. nonreplaceable populations of neurons in birds and mice (Lombardino et al, 2005). Combining LCM with immunocytochemistry could then be used to show how learning alters gene expression within the new neuron itself.…”
Section: Future Directionsmentioning
confidence: 99%